residential complexes - Grigoryeva, Elena (project baikal, 2026)
Living houses, live and life contain the same root.Like many terms in construction and architecture, the expression “residential complex” can take on many meanings, often contradictory. It can be one apartment building or several buildings, it can include all the necessary elements of urban infrastructure or only a part of such elements, its territory can be closed or open, etc. The main idea of the residential complex is to collect everything necessary for people’s daily life in a compact and self-sufficient (integrated) urban planning unit, although this is not always possible.However, the dominance of standard and featureless, sometimes even harmful solutions makes many architects worry about the imperfection of the results of their work in the field of housing. Apartment buildings are grouped into super-dense “human ant-hills”, and here, in the pursuit of profit, developers take no care of safety and health. The developers’ focus on small oneroom apartments and studios, due to their relatively low cost, clearly contradicts the demographic objectives formulated by the state. At the same time, there is a strong trend towards low-rise buildings determined at the government level. The population prefers to live in their own or low-rise houses, and the gigantic territory of Russia disposes to this.Is there a possible balance between these ideological poles?The first issue of Project Baikal journal attempts to discuss these and other issues, which are united under the general theme “Residential Complexes”.
Keywords: residential complex; apartment building; low-rise buildings